1996
DOI: 10.1007/bf00047811
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity, spore recruitment and size in Gelidium sesquipedale (Gelidiales, Rhodophyta)

Abstract: Gelidium sesquipedale fecundity was quantified by counting tetrasporangial sori and cystocarps per meter squared and by estimating the number of spores contained inside them . These were obtained by regression on a size metric of reproductive structures . Tetrasporangial sori length and cystocarp thickness were the best estimators of spore number. To assess spore recruitment, 12 pottery tiles were fixed to the bottom, and the appearance of small fronds was monitored.No clear seasonal pattern of reproduction wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…The reproductive subpopulation of G. sesquipedale of São Rafael, southern Portugal, was dominated by tetrasporic fronds, as described elsewhere for other populations of the same species (Gorostiaga 1990, Salinas 1991, Santos and Duarte 1996 or of the same genus (Montalva and Santelices 1981, Carter 1985, Akatsuka 1986, Macler and West 1987, Santelices 1990, Melo and Neushul 1993, Sosa et al 1993). The G:T ratio of São Rafael reproductive subpopulation varied between 1:7 and 1:10 in the fall, the most fertile season, when up to 61% of the fronds were reproductive.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…The reproductive subpopulation of G. sesquipedale of São Rafael, southern Portugal, was dominated by tetrasporic fronds, as described elsewhere for other populations of the same species (Gorostiaga 1990, Salinas 1991, Santos and Duarte 1996 or of the same genus (Montalva and Santelices 1981, Carter 1985, Akatsuka 1986, Macler and West 1987, Santelices 1990, Melo and Neushul 1993, Sosa et al 1993). The G:T ratio of São Rafael reproductive subpopulation varied between 1:7 and 1:10 in the fall, the most fertile season, when up to 61% of the fronds were reproductive.…”
Section: Discussionsupporting
confidence: 59%
“…Other studies have been reported on the species carposporophyte:tetrasporophyte ratio because inconspicuous spermatangial sori of male fronds were not reported. In a commercially harvested population of the central western coast of Portugal, Santos and Duarte (1996) observed a carposporophyte:tetrasporophyte ratio of 1:10, higher than in São Rafael, where it was up to 1:20 (because half of the gametophytes were carposporophytes). Other commercially harvested populations of G. sesquipedale in northern Spain had carposporophyte:tetrasporophyte ratios of 1:46 (Salinas 1991) and 1:9 (Gorostiaga 1990), indicating no clear effects of harvest on the phase structure of this species.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations